Development of Samiler Jarak-Dolly (SAMIJALI) Business Through Social-Based Business Model - Berto Mulia Wibawa; Andi Hafsah (Institut Teknologi Sepuluh Nopember, 2019)
Samijali is a social-based SME in Surabaya. By conveying the economic issue of the Dolly community as the result from the closure of the Dolly prostitution area. However, the high public interest about Samijali is not in line with the business progress that remain slow. The ability of Samijali to develop it’s capability is still minimal. In addition, the business model owned by Samijali is still very simple when compared with other sociopreneur business models that have rapid development. The aim of this research is to develop Samijali social business model to help improving the competitiveness, develop suitable branding for Samijali based on evaluated SBMC. This research using qualitative methods with inductive-exploratory research designs. In the research phase, researchers conducted interviews with Samijali stakeholders and business experts to formulate an ideal business model for Samijali. From this research, had been agreed on business model design for Samijali by stakeholders Samijali. Hopefully, this research can help Samijali to grow it’s business with the right business model. In addition, this research is expected to make Samijali a role-model for social-based SMEs in Surabaya.